PENGEMBANGAN LKPD BERBASIS KARAKTER KEARIFAN LOKAL PELAJARAN PPKn PADA KELAS IV SD - Fatimah, Iis Daniati; Wiratama, Novialita Angga (LPPM Universitas Muhammadiyah Muara Bungo, 2024)
This research aims to develop learning tools in the form of independent curriculum LKPD based on local wisdom for PPKn subjects in class IV elementary school. Development of local wisdom-based LKPD on regional cultural diversity material using development research (R&D) with 4D design to determine the validity of the research instruments used in the form of interview sheets and validation sheets. design validation, learning on aspects of graphic feasibility with an average score of 6.7, a percentage of 93% included in the